2011
DOI: 10.1007/s10396-011-0328-5
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of tumor vascularity with contrast-enhanced ultrasound for early response of transcatheter arterial chemoembolization for hepatocellular carcinoma: a report of three cases

Abstract: Many contrast-enhanced ultrasound (CE-US) studies have been conducted by qualitative analysis of blood flow, such as classification of enhancement pattern. We evaluated early response of transcatheter arterial chemoembolization (TACE) for hepatocellular carcinoma (HCC) by quantitative analysis of intratumoral vascularity with CE-US in three patients. Three patients (one man, two women) with HCCs were treated in July 2009. CE-US with perfluorocarbon microbubbles (Sonazoid) and CT were performed serially before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Several studies have reported that CEUS could detect viable HCC after TACE more sensitively than CECT. 10,[16][17][18][19][20][21][22][23][24] Although many previous studies have reported the usefulness of CEUS performed more than several weeks after TACE, there are few studies that have reported the usefulness of CEUS for the early evaluation of the treatment response of HCC to TACE. 16,23,24 The aim of this study was to investigate the utility of CEUS for early evaluation of the treatment response of HCC to TACE.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that CEUS could detect viable HCC after TACE more sensitively than CECT. 10,[16][17][18][19][20][21][22][23][24] Although many previous studies have reported the usefulness of CEUS performed more than several weeks after TACE, there are few studies that have reported the usefulness of CEUS for the early evaluation of the treatment response of HCC to TACE. 16,23,24 The aim of this study was to investigate the utility of CEUS for early evaluation of the treatment response of HCC to TACE.…”
mentioning
confidence: 99%
“…Contrast‐enhanced US may therefore have advantages in the early assessment of TACE efficacy in HCC. Several studies have reported that CEUS could detect viable HCC after TACE more sensitively than CECT . Although many previous studies have reported the usefulness of CEUS performed more than several weeks after TACE, there are few studies that have reported the usefulness of CEUS for the early evaluation of the treatment response of HCC to TACE .…”
mentioning
confidence: 99%
“…These defects can be treated by RFA. Kupffer phase Sonazoid ® -enhanced US-guided RFA is possible in almost all cases of HCC that are not identified by B-mode US, with a sensitivity as high as 100% [30][31][32][33][34].…”
Section: Detection Of B-mode Us Undetectable Hcc and Treatment Guidancementioning
confidence: 99%